The Influence of Religious Madrasah Culture on Student Discipline (Pengaruh Budaya Religius Madrasah Terhadap Kedisiplinan Peserta Didik) - R. Suyanto; Agus Pahrudin; Achi Rinaldi (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
This study measures how much the role of madrasah religious culture influences the discipline of Madrasah Aliyah Nurul Iman Sekincau students in West Lampung by using the Mix Method and Sequential Explanatory Design, namely collecting and analyzing quantitative data in the first stage, then followed by collecting and analyzing qualitative data in the first stage. next. Based on the results of the study, the coefficient of determination is shown by R Square = 0.213 which implies that 21.3% of the variability of student discipline variables can be explained by the religious culture of the madrasa (X2), so it can be concluded that the influence of religious culture of the madrasa on student discipline is 21, 3%, while the remaining 78.7% is influenced by other factors. Based on the results of interviews, observations and documentation that the lack of exemplary behavior of teachers and madrasah leaders makes it difficult for students to be disciplined, which then has an impact on negative (deviant) behavior. Therefore, teachers must instill, practice and familiarize Islamic values to their students and provide good role models to them.Keywords: Madrasa Religious Culture, Student Discipline